"Salt Templating": A Simple and Sustainable Pathway toward Highly Porous Functional Carbons from Ionic Liquids. (2nd October 2012) - Fechler, Nina; Fellinger, Tim‐Patrick; Antonietti, Markus
<x xml:space="preserve">Abstract</x> A facile method to fabricate high‐surface area functional carbons via convenient "salt templating" is presented. Exemplarily, nitrogen‐ as well as nitrogen‐/boron‐co‐doped carbons were synthesized using ionic liquids as precursors and eutectics as porogen. The porogen is easily removable with water and the porosities can be adjusted from micro‐ to mesoporous depending on the salt nature and amount. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>